Effectiveness of Mesenchymal Stem Cells and Their Derivatives in Modulating Oxidative Stress in Neurodegenerative Diseases: A Structured Narrative Review - Niken Rahmah Ghanny; Putu Erma Pradnyani; Assyafiya Salwa; Herera Rahajeng; Afifa Radhina; Bunga Anggreini Sari; Ichwan Baihaki (Indonesian Journal of Life Sciences, 2026)
Background: Oxidative stress plays a critical role in the development and progression of neurodegenerative diseases such as Parkinson’s disease (PD), Alzheimer’s disease (AD), and amyotrophic lateral sclerosis (ALS). Mesenchymal stem cells (MSCs) and their derivatives have emerged as promising therapeutic strategies due to their antioxidant, anti-inflammatory, and neuroprotective properties. Objective: This review evaluated the effectiveness of MSC-based interventions in modulating oxidative stress in neurodegenerative disease models. Methods: A structured narrative review search was conducted following PRISMA 2020 guidelines using PubMed and Scopus databases for studies published between 2020 and 2025, with the last search in December 2025. Results: 33 studies met the inclusion criteria, primarily involving Parkinson’s and Alzheimer’s disease models. Overall, MSC-based therapies reduced oxidative stress markers, enhanced antioxidant defenses, activated the Nrf2/HO-1 pathway, improved mitochondrial function, and reduced neuroinflammation in experimental neurodegenerative disease models.